Formação e profissionalização de professores da educação infantil na rede municipal de João Pessoa-PB - Lira, Rejane Maria de Araújo (2017)
This thesis aimed at studying the training and professionalization of the early childhood education teachers. In order to cover this theme, national and local public educational policies and their interaction with the training, professionalization and working conditions of teachers who work in the early childhood education were investigated, focusing on two Childhood Education Reference Centers (CREIs), linked to the Secretariat of Education (SEDEC) of the Municipality of João Pessoa-PB (PMJP). The used methodology is part of a basic research approach, with investigative and descriptive outline, with field strategies, both in relation to the information source and to the place of data collection, longitudinal temporality and predominantly qualitative nature, opting for the interpretive method. To obtain the data, the use of four collection instruments was gathered: observation, field diary, group discussion and individual interviews with 11 (eleven) teachers; 2 (two) managers; 2 (two) supervisors; 8 (eight) monitors; and five (5) nursery teachers. The data were analyzed through the Content Analysis (CA) techniques. From these data, it was highlighted that there are several tensions and complex relationships of confrontations, conflicts, convergences and divergences between the formulation and implementation of the public educational policies analyzed by the training, the professionalization of the early childhood education teacher and the quality of the educational care provided in the Childhood Education Reference Centers (CREIs). The marked disarticulation among these policies and the professional profile found in the CREIs was also highlighted; the professional devaluation was underlined in the precarious wages, in the structure sometimes inadequate for the work, in the teachers´ insufficient and improper training and in the lack of social prestige related to the profession; and the pedagogical practices carried out in the CREIs have confused the sense and the educative aims of the early childhood education, when activities that neglect the indissociability of caring, educating and playing are fulfilled in the understanding that the integration of these aspects is essential for the children´s whole development.